The effects of residual stress on the material characterisation of individual nanowires - MILLS, SHAUN (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2017)
Many of the techniques currently used to measure the mechanical properties of individual nanowires make the assumption that initially the nanowires are in a zero-stress state. However, due to their small sizes and large surface areas, nanomaterials are susceptible to external environmental factors that may influence their measured properties. Therefore, the potential effects that processing and fabrication steps can have on the measured material properties must be considered. In the synthesis of one dimensional nanowires, it is often necessary to passivate the surfaces of these materials to prevent against agglomeration. Using a lateral atomic force microscopy technique, this thesis demonstrates that nanowires passivated with polymer surface coatings can be subjected to a residual stress due to the swelling of the polymer coating when exposed to a solvent medium. Current models used to determine the Young?s modulus of nanowires affected by a residual stress are demonstrated to be problematic. Furthermore, a separate cantilever beam approach is investigated to unambiguously extract the Young?s modulus of stress-free individual nanowires. These cantilever beam measurements are used as a benchmark to compare the validity of Young?s modulus values obtained using the widely used 3-point bending technique. Finally, a unique irreversible stiffening effect in pentagonally twinned silver and gold nanowires is demonstrated using a previously developed electromechanical technique. The Young?s modulus of these nanowires has been shown to increase by up to 70% under current densities of 109 A/m2.
APPROVED
Keywords: nanowires; residual stress; Young's modulus